Challenges and Opportunities in Teaching Mathematics in Timor-Leste’s Primary Schools: A Systematic Review - Salvador Magno Ximenes (Journal of Information System and Education Development, 2026)
The review analyses educational difficulties alongside teaching possibilities that arise within Timor-Leste's primary school mathematics education. Many barriers obstruct effective mathematics teaching despite extensive school improvement initiatives by creating problems with unqualified teachers and limited educational resources, which make student understanding complex because of language barriers. The post-conflict recovery context of Timor-Leste adds more difficulties to the educational system because it has damaged the school infrastructure and teacher development processes. Recent structures of curriculum reform target the modernisation of teaching techniques with peer collaborative initiatives that support educator professional development as administrative forces advance mother tongue-based educational programs for increased student comprehension through native language instruction. This review combines information from ten studies about the current mathematics education status of Timor-Leste, which helps policy leaders and education professionals gain important knowledge. The mathematics education system of Timor-Leste requires special interventions that combine competent teacher training with appropriate financial resources to support teachers in resolving existing difficulties while utilising language effectively for developmental gains